A rare Diagnosis Perforated Gastric Ulcer in a 10 years old Girl, A rare Diagnosis for Age: A case report: Perforated Gastric Ulcer - Shahraki, Ahmad Reza (Student Research in Translational Medicine, 2023)
Perforated gastric ulcer (PGU) is exceedingly uncommon in children. In a child with acute abdomen and Pneumoperitoneum, an Appendiceal etiology is more often suspected as a likely cause. Failure or delay to diagnose a PGU can result in significant morbidity and even mortality. We report a 10 years old girl with abdominal pain for 2 days with PGU. We did examination and we found generalized abdominal pain and performed Laparatomy and we found perforated gastric ulcer and repair with Omental patch. PGU is an uncommon cause of peritonitis in children and poses significant challenges in management. Strong suspicion and prompt appropriate intervention is necessary to avoid untoward outcomes. Researchers conclude that GOO secondary to ulceration can occur in the absence of H. pylori infection. PPU is a rare cause of abdominal pain in children, but still a PUD complication that requires surgery. PPU should be included in the differential diagnosis in patients presenting with acute abdominal pain of uncertain etiology and pneumoperitoneum. Laparoscopy is both diagnostic and therapeutic. Laparoscopic omental patch repair is a safe and effective treatment for PPUs. This case illustrate that perforated peptic ulcers should be considered in children presenting with acute abdomen.